Чи є класифікація синдрому діабетичної стопи на засадах "Міжнародної угоди" кроком до поліпшення наслідків його лікування? - Іващенко, В. В.; Іващенко, А. В. (Clinical Endocrinology and Endocrine Surgery, 2009)
In work on the basis of experience of treatment of 2050 patients with defeats of tissues injuries of the lower extremities attempt of specification of concept of a diabetic foot syndrome is formulated (will be carried out as against the "International agreement") on a principle of safety, or absence of main blood circulation in infinity. In our opinion such approach will promote improvement of the statistical account of these patients and considerably will improve results of treatment.